2006
DOI: 10.1111/j.1567-1364.2006.00081.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of 311Cryptococcus neoformansisolates from a 30-month ECMM survey of cryptococcosis in Europe

Abstract: During a European Confederation of Medical Mycology (ECMM) prospective survey of cryptococcosis in Europe (from July 1997 to December 1999) 655 cases were reported from 17 countries; 565 of the completed questionnaires were evaluable. Cryptococcosis was associated with HIV infection in 77% of cases (range 57.5-94%). Assessment of the laboratory data highlighted the lack of defined standard procedures for the diagnosis of cryptococcosis: the antigen test was not usually used for screening, the disease was mainl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
97
3
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(107 citation statements)
references
References 19 publications
5
97
3
2
Order By: Relevance
“…neoformans has been poorly studied. From the few available studies it is known that serotype D isolates are more prevalent in Europe (27,43). In the current study, only 12% of the clinical isolates were serotype D (Table 3).…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…neoformans has been poorly studied. From the few available studies it is known that serotype D isolates are more prevalent in Europe (27,43). In the current study, only 12% of the clinical isolates were serotype D (Table 3).…”
Section: Discussionmentioning
confidence: 55%
“…When patients with a known immune status were considered, the percentage of HIV-positive patients was 62.8%, which is similar to data from other European studies. A French study showed that 77% (n ϭ 177) of the patients with cryptococcosis were HIV infected (17); in a cohort of 77 Austrian, German, and Swiss patients this was 68% (n ϭ 52) (40), a Spanish study observed 87% (n ϭ 48) (20), and a 30-month European survey reported 77% (n ϭ 435) of HIV-positive patients (43). In the current study, 18 (7.6%) patients were found to have no underlying disease or any other predisposing factors, such as corticosteroid treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that a novel C. neoformans ϫ C. gattii hybrid strain of serotype AB caused a lethal infection in a Canadian AIDS patient (21). Other hybrids of serotypes A and D were recently identified and studied at the molecular level (3,31,108,116,223). While most isolates of serotypes A and D are haploid, AD strains are diploid or aneuploid.…”
Section: Natural Hybrids Between Pathogenic Basidiomycota Yeastsmentioning
confidence: 99%
“…While C. neoformans has a global distribution and is primarily associated with soil contaminated by bat or bird guano (19), C. gattii was until recently thought to be largely confined to tropical and subtropical regions, such as Australia and New Zealand, where it has been found primarily in association with Eucalyptus trees (11). C. gattii has also been isolated from clinical specimens from numerous other parts of the world, including Mexico, parts of Latin America, Europe, southern California, Hawaii, India, and Africa (15,19,25,30).…”
mentioning
confidence: 99%